Ferroelectric‐quasiferroelectric‐ergodic relaxor transition and multifunctional electrical properties in Bi0.5Na0.5TiO3‐based ceramics. Issue 4 (8th November 2017) - Zhou, Changrong; Li, Qingning; Xu, Jiwen; Yang, Ling; Zeng, Weidong; Yuan, Changlai; Chen, Guohua
Abstract: A‐site substituted 0.88(Bi0.5 Na0.5 )1− x (Li0.5 Nd0.5 ) x TiO3 –0.12BaTiO3 (BNTLN x –BT12) ceramics were synthesized using a conventional solid‐state reaction route. The structural transformation and miscellaneous electrical properties were systematically investigated. The A‐site modification induced two sequence transitions from ferroelectric tetragonal ( T ) to quasi‐ferroelectric pseudocubic ( PC ) phase, followed closely by the second transition from non‐ergodic to ergodic relaxor (NR‐ER), and finally to dynamic polar nanoregions (PNRs). The significant enhancement in piezoelectric activity, strain response, broad plateau‐like maximum dielectric permittivity over a large temperature range and energy‐storage level at different compositions may be attributed to the compositionally‐induced T ‐ PC to NR‐ER transition and the alignment of dynamically‐fluctuating PNRs, respectively. The evolution of multifunctional electrical properties, associated with the variations in structure/microstructure, might provide a new insight to investigate the underlying mechanism of structure‐electrical properties relationship in ferroelectric solid solutions.